2020
DOI: 10.1158/1538-7445.sabcs19-p2-08-12
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P2-08-12: Initial real world treatment patterns and outcomes of Abemaciclib for the treatment of HR+,HER2- metastatic breast cancer

Abstract: Background: Abemaciclib is a selective continually dosed cyclin-dependent kinase 4 and 6 (CDK 4&6) inhibitor approved as a single agent and in combination with endocrine therapy for the treatment of HR+,HER2- metastatic breast cancer (MBC). To date, few publications have reported the real world (rw) use of abemaciclib. This retrospective observational study aimed to describe baseline characteristics, treatment patterns, and outcomes among MBC patients treated with abemaciclib in the US. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…For first-line ribociclib plus AI, dose reductions occurred in 55% of patients [49]. The lowest proportion of patients with dose reductions was reported for abemaciclib plus ET in all lines, ranging from 0 to 5.7% [48]. In all lines, the proportion of patients with dose reductions was 6.8% for abemaciclib alone or in combination with ET [48].…”
Section: Dose Reductionsmentioning
confidence: 94%
See 3 more Smart Citations
“…For first-line ribociclib plus AI, dose reductions occurred in 55% of patients [49]. The lowest proportion of patients with dose reductions was reported for abemaciclib plus ET in all lines, ranging from 0 to 5.7% [48]. In all lines, the proportion of patients with dose reductions was 6.8% for abemaciclib alone or in combination with ET [48].…”
Section: Dose Reductionsmentioning
confidence: 94%
“…Median PFS was also reported as not reached in two studies (one study each for abemaciclib [48] and ribociclib [49]). Only one RWE study reported a median PFS for either of the other CDK4/6i: abemaciclib (monotherapy or plus ET) as second-or subsequent-line therapy was associated with a median PFS of 7 months [50].…”
Section: Pfs and Osmentioning
confidence: 99%
See 2 more Smart Citations
“…However, with a median PFS of 33.6 months rather than 22–28 months with palbociclib or with abemaciclib plus AI, and a relative risk reduction in death of 28% in the first-line setting of MONALEESA-3, ribociclib plus fulvestrant seems to be the preferred first-line treatment option in postmenopausal patients [ 19 ]. Moreover, whereas the data on OS for palbociclib and abemaciclib are still immature or are from real-world data of retrospective studies [ 29 , 30 ], the data on OS with ribociclib come directly from phase 3 trials [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%